2017
DOI: 10.1016/s0168-8278(17)31692-6
|View full text |Cite
|
Sign up to set email alerts
|

The risk of early occurrence and recurrence of hepatocellular carcinoma in hepatitis C infected patients treated with direct acting antivirals with and without pegylated interferon: a Belgian experience

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…We also found that, compared to HCV patients receiving DAA therapy with concomitant interferon, those treated without concomitant interferon were generally older and more likely to have had portal hypertension, thrombocytopenia, cirrhosis, renal insufficiency, end‐stage liver disease, mental illness, convulsions, alcoholic liver damage and hepatic encephalopathy, and less likely to have liver enzyme elevations (data not shown). These findings are consistent with other research finding systematic differences in patients who are treated with concomitant interferon vs those who are not, and reflect real‐world clinical practice in which patient characteristics are considered in HCV treatment decisions, highlighting the importance of adjusting for baseline patient characteristics in any examination of the risk of adverse events in treated HCV patients.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that, compared to HCV patients receiving DAA therapy with concomitant interferon, those treated without concomitant interferon were generally older and more likely to have had portal hypertension, thrombocytopenia, cirrhosis, renal insufficiency, end‐stage liver disease, mental illness, convulsions, alcoholic liver damage and hepatic encephalopathy, and less likely to have liver enzyme elevations (data not shown). These findings are consistent with other research finding systematic differences in patients who are treated with concomitant interferon vs those who are not, and reflect real‐world clinical practice in which patient characteristics are considered in HCV treatment decisions, highlighting the importance of adjusting for baseline patient characteristics in any examination of the risk of adverse events in treated HCV patients.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have recently reported an unexpectedly high HCC recurrence rate of 27-29% among subjects treated with liver resection or ablation, who had received DAAs therapy [2][3][4]. However, similar results were not confirmed in other studies [5][6][7][8][9].…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…Some recent studies have shown unexpected high HCC recurrence rates after DAA therapy [2][3][4], but other studies contradicted these findings [5][6][7][8][9]. Given these contrasting data, it is pivotal to identify the patients at a higher risk and to determine the possible mechanisms associated with early occurrence or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 20 studies were excluded because they presented data on HCC occurrence but not recurrence, 11 had insufficient data for abstraction, 5 had overlapping cohorts, 4 exclusively characterised post‐transplant HCC recurrence, and 7 studies were excluded for lack of original data (Figure S1). Finally, review of American Association for the Study of Liver Diseases, European Association for the Study of the Liver, and International Liver Cancer Association conference abstracts identified 7 additional studies and recursive literature searches identified 1 full‐length manuscript and 2 letters to the editor that met inclusion criteria, producing a total of 26 studies . The study by the ANRS collaborative study group included 2 distinct cohorts, yielding a total of 27 cohorts.…”
Section: Resultsmentioning
confidence: 99%